ISLAMIC FINANCIAL TECHNOLOGY TOWARDS THE ADVANCEMENT OF ISLAMIC BANKING IN INDONESIA - Zulfikar, Andi (Sharia Banking Study Program, Faculty of Islamic Economics, Djuanda University, Bogor, 2018)
Responding to the digital economy in the era of industrial revolution 4.0, the quality of sharia banking services in Indonesia is estimated and expected to increase significantly, in order to reach all levels of society, especially for people who live in the 3T area (terdepan/frontier, terluar/outermost, and terpencil/isolated). However, currently the quality of sharia banking services in Indonesia is not yet satisfactory, especially by people living in the 3T area. this research, trying to answer the challenge through a SWOT analysis of the application of financial technology policies in Islamic banks, with the hope of the quality of Islamic banking services can be improved and felt by all levels of Indonesian society and banking players can quickly understand and act. The management of Islamic banking management functions appropriately is based on an attitude of fear of Allah SWT, in the context of managing internal and external assets that include banking activities in a holistic manner. Thus, this study aims to analyze more deeply the strengths, weaknesses, opportunities, and threats (SWOT) of the application of Islamic banking financial technology (mobile banking) in Indonesia, the results showed a significant achievement compared to the previous year, even though in the global context, there were still many breakthroughs needed so that the 3T community could utilize optimal Islamic banking services.